1997
DOI: 10.1097/00004872-199715100-00006
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, serum cholesterol and nutritional state in Tanzania and in the Amazon

Abstract: Transition from a rural to an urbanized lifestyle is accompanied by a rise in the main cardiovascular risk factors; the present data also show that environmental rather than racial factors have a crucial impact on the risk pattern of populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 59 publications
0
20
0
2
Order By: Relevance
“…In contrast, many nonindustrialized countries do not experience increases of blood pressure and hypertension prevalence with age (86, 132,136,160,167,178). A common characteristic of these populations is a low dietary salt intake (43).…”
Section: Agementioning
confidence: 99%
“…In contrast, many nonindustrialized countries do not experience increases of blood pressure and hypertension prevalence with age (86, 132,136,160,167,178). A common characteristic of these populations is a low dietary salt intake (43).…”
Section: Agementioning
confidence: 99%
“…In fact, considering the values obtained for blood pressure, total cholesterol, and nutritional status in populations of 3 continents (Italian urban population, African populations of Tanzania and Uganda, and Amazonian population of Brazil), the African diet poor in salt and rich in fish and vegetables was associated with lower levels of blood pressure, total cholesterol, and body mass index compared not only with those of the Italian population, but also with those of the Brazilian population, which differed from the African diet in regard to the greater consumption of salt and meat 31 . Another study in Tanzania, confirmed the substantial increase in cardiovascular risk as compared with that obtained 10 years before 32 .…”
Section: Lipids (Mg/dl)mentioning
confidence: 93%
“…Intakes of less than 100 mmol/d (2.30 g/d) were reported in China (Province of Taiwan) (Liu & Chung, 1992), Samoa (Galanis et al, 1999), Spain (Schroder, Schmelz & Marrugat, 2002), Uganda and the United Republic of Tanzania (Pavan et al, 1997), and Venezuela (Negretti de Bratter et al, 1998), but these reports were based on a variety of methods including dietary recall, unspecified questionnaire methods and duplicate diets, and none relied on 24-hour urine collections -the validity of these estimates is therefore open to question. In addition, intakes of less than 100 mmol/d (2.30 g/d) were recorded in South Africa from 24-hour recall data, but analysis of data obtained from concomitant 24-hour urine collections gave urinary sodium excretion estimates ranging from 135-165 mmol/d (3.11-3.80 g/d) (Charlton et al, 2005).…”
Section: Intermap Studymentioning
confidence: 99%
“…Approximately equal number of men and women Italy (NS) Pavan et al, 1997 Non-random general population sample from the towns of Mirano and Castelfranco Veneto, stratified by age and sex…”
mentioning
confidence: 99%